Pneumovesicoscopy:An Effective Technique for Urinary Bladder Foreign Body - Pandey, Praveen Kumar; Suruchi, Shukla; Bera, Malay Kumar; Sharma, Pramod Kumar; Singh, Jitendra Pratap (Urology Journal, 2014)